Kinematic study on the run speed kids 11-12 years (Impetus, 2021)
This document studies the kinematic structure of sprinting in children, over a distance of 50 m. 7 girls (11.2 +/- 0.75 years) and 7 boys (11.7 +/- 0.88 years) participated in the study (n = 14). Variables related to step length, step frequency, number of steps, time measurement and speed measurement were studied. The mentioned variables were recorded during the first half of the distance (first 25 m), in the second half of the distance, in the total distance of 50 m and in partial segments every 10 m. The acceleration, maximum cyclical speed and deceleration phases in the 50 m race were identified. After finding the maximum cyclical velocity phase, in each of those evaluated, the angular velocity of the thigh-trunk movement was calculated. The correlation between the maximum angular velocity of the thigh-trunk movement and the level of maximum cyclical running speed, yielded statistical values ​​of strong interrelation (0.7). Consequently, decreased stride frequency appears to be the most important factor contributing to loss of speed with children aged 11 and 12 years.